If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 3 = 2x + 3 Reorder the terms: 3 + -2x = 2x + 3 Reorder the terms: 3 + -2x = 3 + 2x Add '-3' to each side of the equation. 3 + -3 + -2x = 3 + -3 + 2x Combine like terms: 3 + -3 = 0 0 + -2x = 3 + -3 + 2x -2x = 3 + -3 + 2x Combine like terms: 3 + -3 = 0 -2x = 0 + 2x -2x = 2x Solving -2x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x = 2x + -2x Combine like terms: -2x + -2x = -4x -4x = 2x + -2x Combine like terms: 2x + -2x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 647383+8467X-64643+7X= | | 4u=.2 | | Y=2x^2+6x+1 | | Y=3x^2+2x-20 | | 3y=11 | | 10+14=2v-8v | | X(x-10)=3 | | 6x+3(10-4x)=25+8x | | -4x+2=6x-48 | | -x+9=69+5x | | 27x-9=3 | | 3a=9+22 | | 3X+73=6X-8 | | x*x+2x+x+3=x*x+5x+6 | | -2=4x+5x+7 | | 5x+20=14x+4 | | -3-5x=5x-103 | | 2(4x+2)=4(3x+1) | | -6x+2-3x=56 | | 3x+6=17+2x | | 2(3)+y=-1 | | 3x+6=17+2 | | 2(4)+y=-1 | | 5(3)+3y=-6 | | 5(6)+3y=-6 | | 3x^2+8x+5= | | 32u-8-12u=22u-6 | | 2x+10+x+7=x*x+12x+35 | | 1.2x+5=7 | | 4x(x-2)=5 | | y/7=3/14 | | =4x^3y^5 |